Enforcement of Illegal Fishing Laws that was Done by Foreign Ships in the Indonesian Sea Region, Viewed from International Sea Law - Awaliyah, Siti; Gede Sudika Mangku, Dewa; Rai Yuliartini, Ni Putu; Suastika, I Nengah; Ruslan (International Journal of Criminology and Sociology, 2022)
This study aims to determine and examine the law enforcement of illegal fishing and the factors that inhibit law enforcement of illegal fishing conducted by foreign ships in the sea of Indonesia in terms of international maritime law. The type of research used by the authors in this study is a type of normative legal research. Normative legal research is done by examining the object of the form of legislation or legal norms applicable or applied to a particular legal problem. Concerning the type of research used the approach. The results showed that according to the 1982 International Maritime Law Convention (UNCLOS 1982) law enforcement of illegal fishing has been regulated in Article 73 UNCLOS 1982 while in the Indonesian National Law has been regulated in Article 69 Paragraph (4) law Number 45 of 2009 on Fisheries. Further obstacles to law enforcement are the impenetrable enforcement, lack of insight, and the integrity of law enforcement, and the lack of an active role and awareness of the community to assist law enforcement of illegal fishing in the Indonesian marine territory.